A review of current and future food applications of natural hydrocolloids. (25th September 2019) - Yemenicioğlu, Ahmet; Farris, Stefano; Turkyilmaz, Meltem; Gulec, Sukru
Summary: The main aim of this review paper was to focus on current and potential future sources and food applications of natural hydrocolloids in the food industry. The emerging research trends, problems, new methods and alternative approaches in production, environmental concerns, market trends and newly discovered health benefits have been discussed for natural hydrocolloids of commercial relevance. The rheological and surface active properties, interactions, functional properties, films and coatings, encapsulation applications and nanotechnology uses of natural hydrocolloids have been discussed in the light of recent developments. This review also reflected the most up‐to‐date concepts of applying natural hydrocolloids to meet consumer's and food sector's sophisticated demands related to food products. Abstract : Major food applications of natural food hydrocolloids.